Increasing the Role of Culinary Entrepreneurs to Support Tourism on Samalona Island, Makassar City, Indonesia - Ramahadi, Zhafirah; Burhanuddin, Agussalim; Seniwati (Journal of Tourism Sustainability, 2024)
Samalona Island, located in Makassar City, South Sulawesi, is one form of the richness of the diversity of islands in Indonesia. The livelihoods of business actors on this island depend on the number of tourists visiting the island. This study aims to determine how the role of culinary tourism business actors on Samalona Island continues to increase so that they can compete with other culinary tours. This study focuses on culinary tourism as an effort to develop and maintain a positive image of Indonesia in the international world through diplomacy, in this case, maritime diplomacy. Local and foreign tourists often visit this island to enjoy the natural beauty and coastal cuisine offered by business actors on this island. Business actors utilize various facilities on this island to continue managing their finances so that their lives remain sustainable and stable. Samalona Island, as a tourist island in Indonesia, needs to receive significant attention from the government and society so that this island remains one of the tourist choices for tourists who want to enjoy the beauty of the Indonesian maritime. The need for more data analyzing the role of culinary tourism business actors on Samalona Island is a novelty in this study.